1,3-Dimethyl-3′,5-diphenyl-1,5-dihydro-2H,5′H-spiro[furo[2,3-d]pyrimidine-6,4′-isoxazole]-2,4,5′(3H)-trione - Yuliya E. Ryzhkova; Varvara M. Kalashnikova; Fedor V. Ryzhkov; Michail N. Elinson (Molbank, 2022)
Michael addition–halogenation–intramolecular ring-closing (MHIRC) reactions are processes in which a halogen atom as a leaving group can attach to substrates or reactants during the reaction, which then undergoes intramolecular ring closure. In this communication the MHIRC transformation of 4-benzylidene-3-phenylisoxazol-5(4H)-one and 1,3-dimethylbarbituric acid in the presence of N-bromosuccinimide and sodium acetate in EtOH at room temperature was carefully investigated to give novel 1,3-dimethyl-3′,5-diphenyl-1,5-dihydro-2H,5′H-spiro[furo[2,3-d]pyrimi- dine-6,4′-isoxazole]-2,4,5′(3H)-trione in a good yield. The structure of the new compound was confirmed by the results of elemental analysis as well as mass, nuclear magnetic resonance, and infrared spectroscopy.